2017
DOI: 10.1097/nna.0000000000000429
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Nurse Executive in Rural Hospital Closure

Abstract: Between 2010 and June 2016, 75 rural hospitals closed, and more than 250 more are at risk of closure. Nurse executives need to be prepared for this eventuality. There is a need for formal direction on how to close a highly regulated healthcare facility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Prior to and during the process of closure, participants expressed lacking input into hospital‐level administration decisions, similar to Warden's and Probst's (2017) finding of nurse executives reporting exclusion from the decision to close and not feeling prepared for the administrative aspects of a closure once the decision was made. Participants of the present study indicated that nurse executives were burdened with the knowledge of a high likelihood of closure before staff nurses but were unable to share that information immediately.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Prior to and during the process of closure, participants expressed lacking input into hospital‐level administration decisions, similar to Warden's and Probst's (2017) finding of nurse executives reporting exclusion from the decision to close and not feeling prepared for the administrative aspects of a closure once the decision was made. Participants of the present study indicated that nurse executives were burdened with the knowledge of a high likelihood of closure before staff nurses but were unable to share that information immediately.…”
Section: Discussionmentioning
confidence: 76%
“…Community characteristics (i.e., more residents over age 65) have contributed to increased odds of unprofitability for rural hospitals (Kaufman et al., 2016). However, studies providing in‐depth reasons for closures from a qualitative perspective (Hart et al., 1991), and community‐level recommendations regarding preventing closures (Harmata & Bogue, 1997), are dated, and nurses’ insight about closures is limited (Warden & Probst, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results add to few published studies we identified about differences between rural and urban nurse education and work environments (Baernholdt & Mark, ; Skillman et al, ), and extends knowledge by describing how, as hospitals became more rural, there were fewer nurses with a BSN, fewer RNs, and higher patient‐to‐RN ratios. Fewer nursing resources in isolated hospitals represent another worrisome facet of rural population health care access given increasing U.S. rural hospitals closures (Kaufman et al, ; Warden & Probst, ). Results highlight the need for rural health policies to allocate nursing resources to under‐resourced rural populations, who face greater chronic disease that contributes to poorer health compared to urban populations (AHRQ, ; NASEM, ).…”
Section: Discussionmentioning
confidence: 99%